Imamship Tussle in Ekiti State, Nigeria - Olorunda, Balogun Yisa (Transpublika Publisher, 2025)
The selection of Imams has been in existence since the advent of Islam in Ekiti State, Nigeria. The selection takes two dimensions. These are the ones without any problem and those associated with problems. Our focus here is on Imamship tussles that are linked with the appointment of Imams in the State. This will be a continuation of our article on the appointment of Imam in Ekiti State in print. The information used here cut across the three Senatorial districts of the State. That is, Ekiti Central, Ekiti South and Ekiti North. Ikere-Ekiti was chosen in Ekiti South, Igbemo-Ekiti in Ekiti Central and Ikole-Ekiti in Ekiti North Senatorial Districts. The objective of the study is to supplement the existing literatures on the Imamship Tussles in Nigeria. The topic is divided into introduction, composition of Nigeria, creation of Ekiti State, the advent of Islam and Imamship tussles in State. Findings reveal that Imamship tussles in State include the biasness of the Imamship Committees and appointment of the interested person in the position of Imam as an Acting Imam. Among the recommendations are the appointments of learned people in terms of Islam to Imamship Committee and punitive measure for the violators of the State executive order.